The Experimental Performance of an Unglazed PVT Collector with Two Different Absorber Types. (13th August 2012) - Kim, Jin-Hee; Kim, Jun-Tae
Abstract : Photovoltaic-thermal collectors combine photovoltaic modules and solar thermal collectors, forming a single device that produces electricity and heat simultaneously. There are two types of liquid-type PVT collectors, depending on the existence or absence of a glass cover over the PV module. The glass-covered (glazed) PVT collector produces relatively more thermal energy but has a lower electrical yield, whereas the uncovered (unglazed) PVT collector has a relatively low thermal energy and somewhat higher electrical performance. The thermal and electrical performance of liquid-type PVT collectors is related not only to the collector design, such as whether a glass cover is used, but also to the absorber design, that is, whether the absorber is for the sheet-and-tube type or the fully wetted type. The design of the absorber, as it comes into contact with the PV modules and the liquid tubes, is regarded as important, as it is related to the heat transfer from the PV modules to the liquid in the tubes. In this paper, the experimental performance of two liquid-type PVT collectors, a sheet-and-tube type and a fully wetted type, was analyzed.